Wolf - Buyckx, Frederik, 1984- ([Lichtervelde] : Hannibal Books, 2024)
"Photographer Frederik Buyckx (b. 1984) is invariably drawn to places where people still live in close proximity to nature. Far from our overly comfortable society where everything is at our fingertips and we have it all under control. What does a bond with nature mean? And what if freedom, rather than luxury, was central to people's lives? Buyckx abandoned all creature comforts to make WOLF. Over the past decade, he has spent long periods of time in the mountains, in search of answers and inner peace. His wanderings were reflected in a handmade book that he received from his grandfather almost thirty years ago. It contains a fable with accompanying drawings in which Buyckx recognised his own quest for freedom and his affinity with nature. In a series of outstanding images, he captures both its splendour and ruthlessness. Nature doesn't come to order and cannot be tamed; it cuts and it kills."--Publisher information.
Cover title.
In Dutch and English, with some French.
Keywords: Buyckx, Frederik, -- 1984-.; Nature photography